Sosialisasi Aplikasi Pembelajaran Interaktif Berbasis Multimedia - Raden Wirawan; Muhammad Awal Nur (Politeknik Negeri Cilacap, 2021)
The socialization of multimedia-based interactive learning applications is a community service for STMIK Bina Adinata lecturers at Inpres Elementary School Number 207 Linrungloe which aims to increase knowledge and understanding of educators, especially classroom teachers about multimedia-based learning applications. This activity is in the form of counseling about an interactive multimedia-based learning application using a computer. The method used in this service is socialization and training, starting with an explanation of the material about applications, interactive learning, and multimedia, after which an introduction to the use of applications to educators and finally explaining the use of applications to students. The results of this socialization increase the understanding and ability of educators in the application of multimedia-based learning and increase the learning interest of SDI 207 Linrungloe students in the learning process in the classroom using multimedia-based learning applications.